Factors Influencing Nursing Learners in Selecting and Engaging Open and Distance Learning as a Mode of Study for Tertiary Nursing Education ﻿ - Yee , Bit-Lian; Aishah Ali; Raijah A. Rahim; Aini Ahmad; Mohamad Afzhan Khan Mohamad Khalil (2016)
The study aimed to identify factors influencing learners in selecting and engaging in ODL as a mode of study for tertiary nursing education. Face to face data collection with self-administrated questionnaire using convenience sampling with response rate of 208 (64.9%) was used. Regression analysis for significant value for the ANOVA with p> 0.01, show that the result for this study is a valid model. The results indicate that environment factors is a significant variable that influence the OUM nursing learners’ choice in selecting ODL as a mode of study among nursing learners for their tertiary education. Learners that came into the ODL system views the support of technology as the factor that make them chose ODL. (Abstract by authors)